Friends, Cuties and Trash Birds - Salmia, Tiina (Tahiti, 2025)
In this article, I examine human–animal encounters in Instagram selfies with seagulls. I ask how human–seagull relations are visualised, narrated and negotiated in Instagram posts with the hashtag “seagullselfie”. While my total data consist of 814 Instagram posts from before 2020 with #seagullselfie, I have chosen six photographs that represent different types of human–animal interactions for more detailed analysis, as they make visible human ambivalence towards non-human animals. For example, humans sometimes call seagulls “friends”, or even “cuties”, but at other times portray them as hungry, dirty and annoying – as “trash birds”. Drawing on Stacy Alaimo’s concept of trans-corporeal interactions, I focus on the embodied agencies, both human and non-human, and the multispecies sharing of spaces considered “urban” or “natural”. My method of studying the photographs of seagulls and humans is inspired by new materialist “ways of following” art, being moved by photographs and seeing where they take me. I argue that seagulls cross the hierarchical dichotomies of nature and culture and contest the anthropocentric ideals of nature as something that should be accessible on human terms. I claim that there is no beautiful and passive “nature” in the seagull selfies that remains as a background for human action. Instead, in these six photographs, seagulls stalk humans, take their food, photobomb them, refuse to pose for their photographs and ignore their clumsy attempts at friendship.